Nickel–manganese variability in olivine and Al‐in‐olivine thermometry for olivine‐phyric shergottites. (24th July 2021) - Ramsey, Sierra R.; Howarth, Geoffrey H.; Udry, Arya; Gross, Juliane
Abstract: Olivine‐phyric shergottites represent primitive Martian magmas, but they commonly contain excess olivine and rarely represent primary mantle melts. Olivine chemistry, however, tracks magma evolution and preserves information on the original parent magma composition. Here, we investigate the applicability of the Al‐in‐olivine thermometer in tandem with olivine chemistry in a suite of 13 olivine‐phyric shergottites to constrain the compositions and conditions of their mantle sources and parental magmas. We show that the Al‐in‐olivine thermometer is a robust method for constraining crystallization temperatures in shergottites, yielding temperatures in agreement with experimental work. In contrast, we do not recommend olivine–spinel thermometry relying on Mg‐Fe in olivine, which underestimates crystallization temperatures by 160–380 °C. Olivine chemistry reveals distinct differences in Ni concentrations between shergottite groups, with enriched shergottites generally having higher Ni at a given forsterite (Fo) content. Nickel variations in terrestrial olivine are often accredited to contributions from a pyroxenite source; however, the same mechanism is not responsible for Ni variations in Martian olivine. Here, we favor a model for variable olivine modal abundance, caused by multiple melting episodes in the depleted mantle source, affecting Ni partitioning during melting to account for the Ni variations observed. In addition, we show that olivine Ni‐Mn variations in depleted shergottites indicate variable petrogenetic histories and parental magmas. Tissint contains elevated Ni in olivine more similar to the enriched shergottites whereas DaG 1037 has elevated Mn in olivine suggesting an Mn‐enriched parent magma relative to other depleted shergottites.